Low incidence of Peach latent mosaic viroid in peach mother blocks in Serbia - Jevremović, Darko; Paunović, Svetlana (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2014)
Peach latent mosaic viroid (PLMVd) is the causal agent of peach latent mosaic disease that is common on peaches and nectarines worldwide. Most of the isolates do not cause any symptoms on the foliage and the disease may be latent for years. A survey to investigate the presence of PLMVd in selected peach mother blocks in 9 Serbian districts was carried out in 2011 through 2013. A total of 315 trees/samples originating from 43 mother blocks, representing 35 peach and nectarine varieties and 2 rootstocks, were tested by Reverse Transcription - Polymerase Chain Reaction (RT-PCR). PLMVd was detected in 13 samples (4.13%) belonging to 7 varieties and one vineyard peach rootstock. Infected samples were found in 7 mother blocks from 3 districts. Our results indicated a low incidence of PLMVd in the analyzed peach mother blocks.